2022
DOI: 10.37828/em.2022.56.4
|View full text |Cite
|
Sign up to set email alerts
|

A new species Unionicola (Dimockatax stat. rev.) haungthayawensis sp. nov. (Trombidiformes: Unionicolidae) from the freshwater mussel Lamellidens generosus (Gould, 1847) in Myanmar

Abstract: Unionicola (Dimockatax stat. rev.) haungthayawensis sp. nov. is described from the freshwater mussel Lamellidens generosus (Gould, 1847) (Bivalvia: Unionidae). The mites were collected from two sites in Myanmar. The mites were examined morphologically under the light microscope and their mitochondrial COI gene sequences have been obtained. Unionicola (Dimockatax stat. rev.) haungthayawensis sp. nov. is distinguished from another Asian member of the subgenus, U. (D.) tumidoides Vidrine, 1986, by the size of idi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Guided by these considerations, we have recently restored the subgenus Dimockatax when describing the new species, Unionicola (Dimockatax) haungthayawensis [14]. Now, we here restored the valid subgenera in this genus as follows: Unionicola Haldeman, 1842 stat.…”
Section: Subgeneric Taxonomic Concept Of the Genus Unionicolamentioning
confidence: 95%
See 3 more Smart Citations
“…Guided by these considerations, we have recently restored the subgenus Dimockatax when describing the new species, Unionicola (Dimockatax) haungthayawensis [14]. Now, we here restored the valid subgenera in this genus as follows: Unionicola Haldeman, 1842 stat.…”
Section: Subgeneric Taxonomic Concept Of the Genus Unionicolamentioning
confidence: 95%
“…Posterior coxal group without an apparent posterior apodeme, square or rectangular shape with rounded inner corners (females have more rounding along the inner caudal margin). Both male and female genital fields consist of a single pair of acetabular plates; genital acetabula with many pairs (13)(14)(15)(16)(17)(18)(19)(20) concentrated in anterior and posterior groups and may be without a distinct visible border between these groups; leg I with large setae; leg IV rather long, especially IV-L-5 noticeably longer than other segments, tarsus of every leg with bifid claws. Chaetotaxy of walking legs in females and males is different, P-3 with one seta for females and without setae for males; the idiosoma size for females is slightly larger than for males.…”
Section: Taxonomic Accountmentioning
confidence: 99%
See 2 more Smart Citations
“…Chapurina et al (2022a, b) reported a number of species from Lamellidens Simpson, 1900 as gill mites from Myanmar, including U. diversipes, U. (Dimockatax) huangthayaensis (Chapurina et al, 2022b), U. (Myanmaratax) generosa Chapurina, Vidrine, Kondakov, Vikhrev & Bolotov, 2022(in Chapurina et al, 2022a and U.…”
Section: Introductionmentioning
confidence: 99%